A Facile Iodine‐Promoted Enals‐Based cis‐Selective Construction of Aziridine‐2‐aldehyde in Water. Issue 4 (25th January 2019) - Singh, Puneet K.; Verma, Fooleswar; Bhardiya, Smita R.; Singh, Manorama; Rai, Vijai K.; Rai, Ankita
Abstract: Direct I2 ‐catalyzed novel aziridination of [E]‐ cinnamaldehyde using Chloramine–T as nitrogen transfer agent and (BTEAC) as phase transfer catalyst is reported. Operational simplicity, excellent yield of pure products (84‐93%), excellent diastereoselectivity (95‐99%) in favour of cis isomer, ambient reaction conditions and using water as solvent are the salient features of envisaged methodology for direct conversion of enals into tosylaziridines. Abstract : Operationally simple and direct iodine‐promoted nitrene insertion into olefin of [E]‐ cinnamaldehyde using Chloramine–T as N‐ Ts reagent in water is reported in high yield (84‐93%) and excellent diastereoselectivity (95‐99%) in favour of cis isomer.